2020
DOI: 10.1111/codi.15009
|View full text |Cite
|
Sign up to set email alerts
|

Early detection and follow‐up of colorectal neoplasia based on faecal volatile organic compounds

Abstract: Aim Early detection and removal of colorectal cancer (CRC) and advanced adenomas (AAs) decreases the incidence of and mortality from the disease. We aimed to evaluate the potential of faecal volatile organic compounds (VOCs) for detection and follow-up of colorectal adenoma using advanced electronic nose technology. Method This was a prospective multi-centre case-control cohort including two district hospitals and one tertiary referral hospital. Patients undergoing colonoscopy were instructed to collect a faec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Only two studies used GC-MS and were able to identify specific VOCs [ 49 , 50 ]. Bosch et al [ 50 ] reported that fecal VOCs could discriminate CRC patients from the controls with an AUC of 0.96.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies used GC-MS and were able to identify specific VOCs [ 49 , 50 ]. Bosch et al [ 50 ] reported that fecal VOCs could discriminate CRC patients from the controls with an AUC of 0.96.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, Gas chromatography-mass spectrometry (GC-MS), which is a chemical analytical technique, is considered the ongoing gold standard in VOC detection [52], but on the other hand, VOC sensors are getting more and more relevance because they are inexpensive, often portable, and easy to use [109]. This is why findings such as the ones listed in Table S7 (Supplementary material) could represent the next frontier for large population-based screening programs [50][51][52][53][54][55][56][57][58].…”
Section: Volatile Organic Compounds (Vocs) 271 Stool Vocsmentioning
confidence: 99%
“…When looking at these results, we should notice some limitations: Current studies are limited to case control and cohort studies, not taking into consideration a real screening setting. Also, due to their complex interaction in the gut, external factors such as diet and medications play a role in VOCs profiling [50] and they are often not deeply analysed before proceeding into the CRC-control differentiation. Nonetheless, these studies highlight the potential of FAIMS in analyzing Urinary VOCs for CRC detection.…”
Section: Field Asymmetric Ion Mobility Mass Spectroscopy (Faims)-based Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…GC-IMS (Gas Chromatography-Ion Mobility Spectrometry) is one such technique, it provides high sensitivity and selectivity, and the GC-IMS can be created in a portable form factor and can use nitrogen or air as the carrier gas. Our group has reported the use of this method with a range of different diseases 28,29 .…”
Section: Introductionmentioning
confidence: 99%